PENGARUH KEPEMIMPINAN, PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN RUMAH SAKIT ISLAM NAHDATUL ULAMA DEMAK (RSI NU DEMAK - Ririn Afidah, 13.05.51.0030 (Students' Journal of Economic and Management, 2017)
This research is a research that examines the influence of leadership, training and work discipline with the perspective of Human Resource Management theory. The purpose of this study is to prove the influence of leadership, training and work discipline on the performance of Islamic Hospital staff Nahdatul Ulama Demak (RSI NU Demak). The technique of determining the sample using purposive sampling, while sampling technique using Slovin formula obtained 75 respondents. Data analysis used is the test of validity, reliability and multiple regression. While the hypothesis test tool using t and F test. The results showed that leadership, training and work discipline partially or simultaneously have a positive and significant effect on performance. Leadership has the greatest influence on performance. Leadership, training and work discipline contributed to the performance of 90.6%. Keywords: Leadership, training, work motivation and performance